2020
DOI: 10.1080/07391102.2020.1842246
|View full text |Cite
|
Sign up to set email alerts
|

Traditional medicinal plants against replication, maturation and transmission targets of SARS-CoV-2: computational investigation

Abstract: COVID-19 is an infectious pandemic caused by the SARS-CoV-2 virus. The critical components of SARS-CoV-2 are the spike protein (S-protein) and the main protease (M pro ). M pro is required for the maturation of the various polyproteins involved in replication and transcription. S-protein helps the SARS-CoV-2 to enter the host cells through the angiotensin-converting enzyme 2 (ACE2). Since ACE2 is required for the binding of SARS-CoV-2 on the host cells, ACE2 inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 57 publications
(72 reference statements)
1
23
0
Order By: Relevance
“…These SARS-CoV-2 target proteins have been used in several investigations to identify therapeutics against COVID-19 [ 13 , [18] , [19] , [20] , [21] ]. The protein molecules were processed by removing crystallographic water molecules, adding polar hydrogens, followed by stabilizing the charges as demonstrated earlier [ 22 , 23 ]. Finally, the three-dimensional coordinates were converted into PDBQT format using ADT [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These SARS-CoV-2 target proteins have been used in several investigations to identify therapeutics against COVID-19 [ 13 , [18] , [19] , [20] , [21] ]. The protein molecules were processed by removing crystallographic water molecules, adding polar hydrogens, followed by stabilizing the charges as demonstrated earlier [ 22 , 23 ]. Finally, the three-dimensional coordinates were converted into PDBQT format using ADT [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Molecular docking was carried out using AutoDock-Vina [ 24 ]. Grid boxes were created around the active sites of SARS-CoV-2 3CL pro , PLpro, RdRp, helicase, and the interacting crucial residues of the SARS-CoV-2 spike protein-human ACE2 receptor complex using Autodock tools with dimensions relative to the ligands (XYZ) with a resolution of 1 Å [ 22 , 23 , 25 ]. Each docking calculation was performed three-times using different seeds and retaining the remaining values as default.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also showed that natural compounds can interact with the catalytic site of M pro proteases at HIS41 and CYS145 [24,29]. Previous research indicated that binding energy of -7.0 kcal/mol or less could be effective against SARS-CoV-2 which causes COVID-19 [26].…”
Section: Screening Process and Molecular Docking Analysismentioning
confidence: 99%
“…Despite recent availability of vaccine for prophylaxis, massive efforts are ongoing for the discovery of novel drugs for the treatment and prevention of COVID-19 (Jean and Hsueh, 2020;Kandeel and Al-Nazawi, 2020;Rabaan et al, 2020;Singh et al, 2020). In parallel with repurposing modern medicines, there are numerous attempts to explore natural products with potential to target the interplay of viral infection and immune-inflammatory axis (Bahramsoltani and Rahimi, 2020;Basu et al, 2020;Benarba and Pandiella, 2020;Hensel et al, 2020;Mondal et al, 2020;Narkhede et al, 2020). Over the past few months it has been suggested that natural products hold great promise in the management of COVID-19 due to their antiviral, anti-inflammatory, and immunomodulator activities (Bahramsoltani and Rahimi, 2020;Basu et al, 2020;Benarba and Pandiella, 2020;Mondal et al, 2020;Narkhede et al, 2020).…”
Section: Introductionmentioning
confidence: 99%